Convex conservation laws with discontinuous coefficients. existence, uniqueness and asymptotic behavior - Klingenberg, Christian; Risebro, Nils Henrik (Communications in partial differential equations, 1995)
Existence and uniqueness is proved, in the class of functions satisfying a wave entropy condition, of weak solutions to a conservation law with a flux function that may depend discontinuously on the space variable. The large time limit is then studied, and explicit formulas for this limit is given in the case where the initial data as well as the x dependency of the flux vary periodically. Throughout the paper, front tracking is used as a method of analysis. A numerical example which illustrates the results and method of proof is also presented.
Elektronische Reproduktion der Druck-Ausgabe 18. November 2011
Gesehen am 22.05.2023